2000
DOI: 10.1111/j.1749-6632.2000.tb06240.x
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia Screening‐Yes, but of Whom, When, by Whom, and with What?

Abstract: The importance of screening programs in reducing the prevalence of genital chlamydial infections is stressed by the fact that the majority of infected persons are more or less asymptomatic. The use of oral contraceptives may mask infections affecting the upper genital tract. This imposes selective screening and rescreening of women with a history of pelvic inflammatory disease. The recent knowledge that vaginal introital samples will provide a detection rate equal to or even higher than that of cervical sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…[31] The rate of chlamydial infecstrategy. [11,43,47] A review of the cost effectiveness of screening tions among infants who received silver nitrate was 92.5% higher reported that screening of asymptomatic women under 30 years of than among those assigned to receive povidone-iodine; the rate age was cost effective at prevalence rates of more than 3%.…”
Section: Prenatal Screeningmentioning
confidence: 99%
See 2 more Smart Citations
“…[31] The rate of chlamydial infecstrategy. [11,43,47] A review of the cost effectiveness of screening tions among infants who received silver nitrate was 92.5% higher reported that screening of asymptomatic women under 30 years of than among those assigned to receive povidone-iodine; the rate age was cost effective at prevalence rates of more than 3%.…”
Section: Prenatal Screeningmentioning
confidence: 99%
“…[43] In developing couna historical control group, the rate of transmission of chlamydial tries this is frequently not possible. The cost of screening and infection was reduced by 63% with silver nitrate and 77% with treatment of infected carriers must be weighed up against the cost tetracycline (table I).…”
Section: Prenatal Screeningmentioning
confidence: 99%
See 1 more Smart Citation